2021
DOI: 10.1016/j.ijid.2021.02.115
|View full text |Cite
|
Sign up to set email alerts
|

Main differences between the first and second waves of COVID-19 in Madrid, Spain

Abstract: Background: The emergence and rapid global spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) represents a major challenge to health services, and has disrupted social and economic activities worldwide. In Spain, the first pandemic wave started in mid-March 2020 and lasted for 3 months, requiring home confinement and strict lockdown. Following relaxation of the measures during the summer, a second wave commenced in mid-September 2020 and extended until Christmas 2020. Methods: The two pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 8 publications
4
94
3
1
Order By: Relevance
“…In our study the association between glucocorticoid treatment and hospital readmission was remarkable. Since there was no generalized prescription of corticosteroids during the first wave, we cannot rule out that this treatment was a surrogate marker of greater pulmonary involvement predisposing to hospital readmission 25 . In addition, a positive association was found in the univariant analysis between macrolide treatment and a reduction in risk of hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the association between glucocorticoid treatment and hospital readmission was remarkable. Since there was no generalized prescription of corticosteroids during the first wave, we cannot rule out that this treatment was a surrogate marker of greater pulmonary involvement predisposing to hospital readmission 25 . In addition, a positive association was found in the univariant analysis between macrolide treatment and a reduction in risk of hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany (April–June 2020), seropositivity was 0.97% using ELISA, and 0.36% using VNT [ 20 ]. Significantly higher seropositivity was observed after the second pandemic peak, varying from 11.4% in Poland (October–November 2020) [ 21 ], and 19.3% in Spain (Madrid, at the end of 2020) [ 22 ], to 21.1% in Switzerland (Geneva, November–December 2020) [ 23 ]. In Slovenia, the seroprevalence after the first (April 2020) and second (October–November 2020) waves was found to be 2.78% and 4.06%, respectively [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the overall concern for the spread of the B.1.1.7 variant, which has been reported to cause a more severe illness as compared to previous SARS-CoV-2 viruses [ 1 , 2 , 3 ], COVID-19-associated mortality has not increased in parallel to the new surge of infections. Additionally, some studies performed in Italy and Spain observed a lower pathogenicity of COVID-19 in the second epidemic wave as compared to the first wave [ 4 , 5 ]. Several factors may have contributed to the current relative decrease in COVID-19 infection to mortality ratio as compared to the first wave.…”
Section: Introductionmentioning
confidence: 99%